1997
DOI: 10.1021/om970005d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structural Characterization of closo- and exo-nido-Lanthanacarboranes

Abstract: Treatment of anhydrous LaCl3 with 1 equiv of Na2[7,8-R2-nido-7,8-R2C2B9H9] in THF afforded sandwich complexes closo-{(THF)2Na}{(R2C2B9H9)2La(THF)2} (R = H (1), R = C6H5CH2 (2)) in good yield. Reaction of SmI2 with an equimolar amount of Na2[7,8-nido-7,8-(C6H5CH2)2C2B9H9] in THF, followed by the addition of 1,2-dimethoxyethane (DME), generated the dimeric exo-nido-[((C6H5CH2)2C2B9H9)Sm(DME)2]2·DME (3) in 70% yield. All complexes were characterized by 1H, 13C, and 11B NMR and IR spectroscopy as well as complexom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
45
0
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 29 publications
3
45
0
2
Order By: Relevance
“…192 In the case of the smaller lanthanides Y and Yb, a half-sandwich lanthanacarborane chloride seems to be formed. But only the recrystallization product from a wet THF solution was characterized for Yb, which is the ionic compound [YbCl 2 -(THF) 5 ][nido-C 2 B 9 H 12 ] (108).…”
Section: B 9 Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…192 In the case of the smaller lanthanides Y and Yb, a half-sandwich lanthanacarborane chloride seems to be formed. But only the recrystallization product from a wet THF solution was characterized for Yb, which is the ionic compound [YbCl 2 -(THF) 5 ][nido-C 2 B 9 H 12 ] (108).…”
Section: B 9 Derivativesmentioning
confidence: 99%
“…Bonding occurs to the Sm atoms via two B-H bonds from the upper and two from the lower CB belt, respectively. 192 Treatment of 2 equiv of Na 2 [(C 6 H 5 CH 2 ) 2 C 2 B 9 H 9 ] with divalent Sm and Yb gives isomorphous structures [exo-nido-{(C 6 H 5 CH 2 ) 2 C 2 B 9 H 9 }Ln(THF) 3 ] 2 (110, Ln ) Sm, Yb), where the bonding situation is more complicated. The metal atoms are bonded to both belts and there again in different fashions as well.…”
Section: B 9 Derivativesmentioning
confidence: 99%
“…As these compounds are isoelectronic with their respective Cp analogues, one would expect similar, but polar group tolerable, catalytic behaviors in the polymerization of a-olefins. The coordination chemistry of carborane clusters derived from the carborane cages systems has been widely studied, and substituted and unsubstituted dicarbollide metal complexes have been reported [14][15][16][17][18][19][20]. However, to the best of our knowledge, the study of carborane trianion-based metallocene analogues is limited with only a few reported examples [21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…The study of the coordination chemistry of carborane clusters derived from the 1-R-2-R 0 -1,2-C 2 B 10 H 10 and 2-R-n-R 0 -2,n-C 2 B 4 H 6 (n ¼ 3, 4; R, R 0 ¼ H or a C ðcageÞ derivative) cage systems have most often been studied separately [1][2][3][4][5][6][7]. Since each cage system offers its own attractions, the targeted syntheses of specific linkedcarborane compounds containing both large and small coordinating cages capable of having charges ranging from )1 to )4 could lead to a series of ligands having unique properties.…”
mentioning
confidence: 99%